2018
DOI: 10.21037/jtd.2018.08.124
|View full text |Cite
|
Sign up to set email alerts
|

Expression and pathological significance of CC chemokine receptor 7 and its ligands in the airway of asthmatic rats exposed to cigarette smoke

Abstract: Background: Cigarette smoking aggravates the symptoms of asthma, leading to the rapid decline of lung function. Dendritic cells (DCs) and lymphocytes are considered initiating and promoting factors for the airway inflammation reactions of asthma. In addition, activation of CC chemokine receptor 7 (CCR7) by chemokine (C-C motif) ligand (CCL) 19 and 21 promotes DCs and T cells migration to lymphoid tissues during inflammation. We aimed to examine how cigarette smoke affects the expression of CCR7 in the lungs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It was found that smoking may correlate with elevated CCR7 mRNA expression level [26], that CCR7 plays a major role in modulating inflammatory responses in airways in pulmonary diseases [27], and that cigarette smoking upregulates CCR7, CCL19, and CCL21 mRNA expression levels in lymph nodes of wild-type mice [28]. It was also concluded that exposure to cigarette smoke can upregulate the number of DCs and cause immunoreactions through CCR7mediated chemotaxis [29]. Surpassingly, in the NSCLC patients in the present study, higher CCR7 and CCL19 expression levels were observed in non-smokers than in smokers; indeed, cigarette smoke extract (CSE) was found to suppress CCR7 expression on DCs in the lungs of smokers, but not diminish their migration towards a CCR7 ligand [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that smoking may correlate with elevated CCR7 mRNA expression level [26], that CCR7 plays a major role in modulating inflammatory responses in airways in pulmonary diseases [27], and that cigarette smoking upregulates CCR7, CCL19, and CCL21 mRNA expression levels in lymph nodes of wild-type mice [28]. It was also concluded that exposure to cigarette smoke can upregulate the number of DCs and cause immunoreactions through CCR7mediated chemotaxis [29]. Surpassingly, in the NSCLC patients in the present study, higher CCR7 and CCL19 expression levels were observed in non-smokers than in smokers; indeed, cigarette smoke extract (CSE) was found to suppress CCR7 expression on DCs in the lungs of smokers, but not diminish their migration towards a CCR7 ligand [28].…”
Section: Discussionmentioning
confidence: 99%
“…One such variant is rs112401631 (chr17:40608272:T:A), a fine-mapped variant for asthma (PIP = 0.27) that colocalizes with an eQTL chr17:40600717:G (PP.H4 = 0.9022; coloc 23 ) linked to CCR7 gene in the lymphoblastoid cell line 23 , 24 . The CCR7 gene is well-known for its role in the homing of T cell populations to lymphoid organs 25 , 26 , and CCR7 + memory CD4 + T cells have previously been associated with severity of asthma 27 , 28 . In PBMC data, the tile underlying rs112401631 was predicted to be significantly linked to the CCR7 gene in various T cell subtypes (CD8 effector with FDR-adjusted P = 3.7 × 10 −08 , CD4 memory with FDR-adjusted P = 5.9 × 10 −21 , CD8 naive with FDR-adjusted P = 7.6 × 10 −18 and CD4 naive with FDR-adjusted P = 2.2 × 10 −17 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our data, CCL4 expression is linked with poor prognosis in cancer [ 45 ]. On the other hand, cigarette smoking has been shown to increase blood and bronchoalveolar lavage fluid levels of the CCR7 ligands CCL19 and CCL21 [ 46 ], thereby contributing to migration of lung cancer cells [ 47 ]. Additionally, previous research has considered CCL21 in oral cancer as a candidate marker for unfavorable outcome [ 48 ].…”
Section: Discussionmentioning
confidence: 99%